The bright side of financial derivatives: Options trading and firm innovation - Blanco, Iván; Wehrheim, David (Journal of Financial Economics, 2017)
Do financial derivatives enhance or impede innovation? We answer this question by examining the relationship between equity options markets and standard measures of firm innovation. We find that firms with more options trading activity generate more patents and patent citations per dollar invested in research and development (R&D), after accounting for other confounding factors. These results are confirmed when we use a propensity score matching procedure and an instrumental variable approach to control for the potential endogeneity of options trading. The evidence is consistent with the notion that the enhanced informational efficiency induced by options leads to an improved allocation of corporate resources. We further discuss possible underlying economic mechanisms through which more active options markets boost innovation and show that the effect remains substantial even after controlling for these mechanisms. Considering the average increase in the dollar volume of options traded for our sample firms, we conclude that a 200% move in options volume increases firm innovation by about 31%.